An Analysis of Errors in Writing the Descriptive Text "My Family": A Literacy Study of First Semester Student at Communication Studies Program-Institute of Mpu Kuturan Singaraja - Gusti Ayu Putu Diah Permata Sari AR (The Future of Education Journal, 2026)
This study aims to analyze the errors made by first-semester students of the Communication Studies Program at the Institute of Mpu Kuturan Singaraja in writing a descriptive text entitled My Family. The type of this research is descriptive qualitative research which is explains the error from the student. After collecting the data, the researcher found the types of lexical error, syntactical error, and discourse error based on the students’ worksheet. In this research, the researcher collecting the data use elicitation technique which include six steps. After the data are collected, the writer analyzes the data by using following steps namely classifying the error, describing the frequency of errors, describing the dominant type of error, and describing the sources of error. The result of the research showed the dominant error of students is lexical error especially in the wrong spelling. Meanwhile, the source of error divided into two types namely interlingual transfer and intralingual transfer. From a writing literacy perspective, the findings indicate that the students are still developing their ability to produce accurate, coherent, and meaningful descriptive texts in English. The identified lexical, grammatical, and discourse errors affected the clarity and effectiveness of their written communication.